Cetaceans of north-western continental Africa (Morocco to Liberia): diversity and distribution - Correia, Ana M.; Mihova, Marieta; Gil, Ágatha; Oliveira-Rodrigues, Cláudia; Afonso, Luís; Valente, Raul; Rosso, Massimiliano; Sousa-Pinto, Isabel; Pierce, Graham J. (Frontiers in Marine Science, 2024)
The north-western coast of Africa is one of the most productive marine systems in the world, where a high diversity of cetacean species has been recorded. However, management of human activities that impact cetacean populations in the area is inadequate, in part due to poor knowledge on cetacean occurrence and the lack of systematic surveys. We reviewed existing knowledge on cetacean distribution between Morocco and Liberia and analyzed the spatial and temporal distribution of records, as well as species occurrence, further discussing the reported distribution ranges. The systematic literature review included 39 sources reporting on 36 species in the area, with a total of 2241 sightings and 2178 non-sighting records. Delphinus delphis (common dolphin) and Tursiops truncatus (bottlenose dolphin) are the two species with the highest number of sources reporting on them. This review reveals a spatially and temporally heterogeneous coverage of the area in the literature and published data on cetacean occurrence. In summary, although most of the compiled sources are recently published (2011-2020), the majority of records are from prior to 2000. In several range states, especially south of Senegal, little information is available. Therefore, the available information is unlikely to represent the current status of cetacean communities in the region. It is essential to fill knowledge gaps by increasing the collection of cetacean distribution data in the area, in order to support effective conservation measures and ensure sustainable utilization of the living marine resources in this rapidly developing region.